394 Sentinel lymph node mapping vs systematic lymphadenectomy for endometrial cancer: surgical morbidity and lymphatic complications. (18th September 2019) - Accorsi, G; dos Reis, R; Schmidt, R; Lacerda, L; Vieira, M; Andrade, C
Abstract : Objectives: Sentinel lymph node (SLN) mappinghas been proven to accurately stage endometrial cancer (EC). However, there is a lack of studies comparing the incidence of complications between different lymph node approaches in EC. Our objective is to define the complication rates of SLN biopsy in EC patients. Methods: We retrospectively analyzed all patients with EC surgically treated at Barretos Cancer Hospital between April 2013 and March 2018. We evaluated intraoperative complications and 30-day complications using the Memorial Sloan Lettering Cancer Center's Surgical Secondary Events Grading System, separating the patients into four groups: hysterectomy (HT); hysterectomy plus pelvic lymphadenectomy, with or without para-aortic dissection (HT+LND); hysterectomy plus sentinel biopsy (HT+SLN); and hysterectomy plus lymphadenectomy and sentinel biopsy (HT+SLN+LND). Results: As compared with the HT group, the HT+SLN group did not show any increased risk of complications in terms of intraoperative injury (0vs1; p =1.0) and 30-day complications (8vs7; p =0.782).The HT+LND group had an increased surgical time (370 min, p <0.001), greater intraoperative blood loss (100cc, p <0.001), and a higher incidence of injury during surgery (7%, p =0.005) and any 30-day complication (38.2%, p =0.002) as compared with HT+SLN. Performing LND was associated with a greater risk of 30-day complications (hazard ratio [HR]:14.25; 95% confidence interval [CI]:1.85–19.63) and intraoperative injury (HR:3.11; 95% CI:1.62–5.98). Conclusions: SLN mapping does not increase morbidity in the surgical treatment of EC patients, and compared with comprehensive lymphadenectomy, it has a lower risk of complications. Our findings support the use of the SLN algorithm in EC patients.